Numerical modeling and simulation in various processes - ISBĂŞOIU, Eliza Consuela (Annals of Spiru Haret University. Economic Series, 2011)
The modeling and simulating of the economic processes is situated at the border of mathematics and technique of calculation. It deals with the substantiation of the managerial decision with efficiency for the producer, with the help of some flexible economic-mathematics models; they also offer the possibility of using the simulation technique. The economic modeling offers the manager the rigorous side of his actions, multiple chances in order to connect existing resources with the objectives pursued for a certain period of time, offering the possibility of a better and faster thinking and deciding process, without deforming the reality.